Hydrocephalus Indian scenario – A review - Venkataramana, N. K. (Medknow Publications, 2011)
Hydrocephalus is a common clinical problem seen in pediatric neurosurgical practice. Hydrocephalus involves dilatation of the cerebral ventricular system with corresponding, compressive effects on the parenchyma. It can be communicative or obstructive types. Congenital, acquired, infective, and secondary hydrocephalus have different clinical features with different modality of treatments. Ventriculoperitoneal shunt is the gold standard of treatment. Endoscopic 3(rd) ventriculostomy is rapidly gaining prominence as an alternative. Various kinds of hydrocephalus, their pathophysiology, treatment and complications are reviewed.